Implementasi Ice Breaking dalam Meningkatkan Minat Belajar Siswa di SDN 64/I Teratai - Violyta Putri Nanda; Nur Anisa Rahman; Syahrial Syahrial; Silvina Noviyanti (AS-SABIQUN, 2022)
This study aims to identify and describe the implementation of chants in increasing student interest in learning at SDN 64/I Teratai, describing the implementation of games in increasing student interest in learning, and describing the implementation of exercise in increasing student interest in learning at SDN 64/I Teratai. The approach used is a qualitative approach. The subjects of this study were fifth grade students at SDN 64/I Lotus. Research data sources consist of informants, and documentation. Data collection techniques with observation, in-depth interviews, and documentation. Research data analysis includes, 1). Data collection, 2). Organizing or grouping the collected data according to the nature of the existing categories. Data analysis was carried out through four stages including, 1). Data reduction, 2). Data presentation, 3). Verification and conclusion. Meanwhile, checking the validity of the data is done by using the triangulation technique of data sources. The results of this study, are (1) the implementation of yells in increasing student interest in learning at SDN 64/I Teratai, namely using yells when learning in class, yelling is applied when class conditions start to be less conducive. The teacher invites students to sing yells as a distraction. Students can also make chants individually or in groups with a duration of about 3-5 minutes. (2) the implementation of games in increasing student interest in learning at SDN 64/I Teratai is to make learning more interesting and fun, so games can be used that can build children's concentration to be able to think, act, and refocus on the material so that children's interest in learning is more good and easy to digest lessons. (3) the implementation of exercise in increasing student interest in learning at SDN 64/I Teratai, namely in implementing exercise, it is carried out when students look sluggish after sitting for a long time just listening to the explanation of the material that the teacher conveys, then with exercise the blood flow will become smooth again so that the thinking process of students is fresher and more effective. Teachers can creatively use variations of body movements.